Therapeutic nihilism of neurological diseases: A comparative qualitative study. (November 2019) - Sedney, Cara; Kurowski-Burt, Amy; Smith, Matthew; Dekeseredy, Pat; Grey, Carl; Boo, SoHyun
Highlights: The perception of futility can affect the healthcare environment. The perceived ability of the patient to recover was the most cited reason for aggressive measures. Differences in decision making can significantly affect healthcare team dynamics. Abstract: Objective: The notion of therapeutic nihilism may lead to early removal of care based upon perceived poor prognosis. The goal of this study was to examine if differences for nihilism perspectives exist between professions and within professions at the different levels of experience and exposure to neurological conditions. Method: Survey methods was used to assess perception of care futility and therapeutic nihilism using six case-based scenarios followed by five questions regarding practitioner care choices and perspective. Participants were student and professional occupational and physical therapists, nurses, and doctors (n = 110). Thematic analysis was completed to determine influences on patient care. Results: Six themes (quality of life, provider experience, prognosis/treatability, medical details, patient's age, and family/patient wishes) emerged that influenced treatment decisions across all participants. All provider groups reported prognosis and treatability as their number one factor for treatment decisions, then therapists mentioned QOL most, nurses cited age, and doctors said medical details. Differences between students and professionals were also apparent. Discussion: The perceived ability of the patient to recover (prognosis/treatability) with medical care was the most commonly cited reason for aggressive measures, with quality of life, medical details, and patient age also representing strong themes across disciplines and level of training.